The Semantic Web and Web Science 8th Chinese Conference, CSWS 2014, Wuhan, China, August 8-12, 2014, Revised Selected Papers - Zhao, Dongyan; Du, Jianfeng; Wang, Haofen; Wang, Peng; Ji, Donghong; Pan, Jeff Z. (Springer eBooks, 2014)
This book constitutes the thoroughly refereed papers of the 8th Chinese Conference on The Semantic Web and Web Science, CSWS 2014, held in Wuhan, China, in August 2014. The 22 research papers presented were carefully reviewed and selected from 61 submissions. The papers are organized in topical sections such as ontology reasoning and learning; semantic data generation and management; and semantic technology and applications.